Development and evaluation of an early specialised traumatic brain injury vocational rehabilitation training package - Holmes, Jain; Phillips, Julie; Morris, Richard; Bedekar, Yash; Tyerman, Ruth; Radford, Kathryn (Sage, 2016)
Background: In a feasibility randomised controlled trial, training was developed to equip Occupational Therapists to deliver Early Specialised Traumatic Brain Injury Vocational Rehabilitation in the English National Health Service.